The Rise and Fall of Gaming Houses: Content Creation, Precarity, and Professionalization in Esports - Benn, Adam (Loading, 2025)
This article examines the evolution of gaming houses in esports as physical manifestations of the industry's shifting relationship with labor, capital, and professionalization. By tracing the transformation of these communal living spaces from grassroots solutions to economic precarity into corporate-managed professional environments, the analysis highlights complex tensions between passion and exploitation that characterize digital labor. Drawing on theoretical frameworks from digital labor studies alongside ethnographic interviews with 33 industry professionals, this research positions gaming houses as both architectural responses to precarity and spatial embodiments of the blurred boundaries between play and work that define esports. The analysis reveals that while the aesthetic progression of gaming houses from makeshift accommodations to state-of-the-art facilities suggests industry maturation, underlying conditions of employment insecurity persist.